2001
DOI: 10.1034/j.1600-0714.2001.030008471.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral pseudomembranous candidiasis, herpes simplex virus‐1 infection, and oral mucositis in head and neck cancer patients receiving radiotherapy and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) mouthwash

Abstract: Oral pseudomembranous candidiasis (OPC) was evaluated in 61 patients receiving head and neck radiotherapy (RT). Herpes simplex virus-1 (HSV-1) reactivation was also investigated in 14 patients. According to the agreed protocol, granulocyte-macrophage colony-stimulating factor (GM-CSF) mouthwash was administered in 46 patients with radiation-induced ulcers. Candidiasis was diagnosed in 31 patients. Candida albicans was the most frequent isolate. Multiple Candida species were isolated from the lesions of four pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
1
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 24 publications
10
65
1
8
Order By: Relevance
“…This may happen due to inclusion of different tumour types, patients with different protocol treatments for RT and/or chemotherapy, collection of oral rinsing samples performed at distinct moments, and lack of serological data [16,17,26]. …”
Section: Discussionmentioning
confidence: 99%
“…This may happen due to inclusion of different tumour types, patients with different protocol treatments for RT and/or chemotherapy, collection of oral rinsing samples performed at distinct moments, and lack of serological data [16,17,26]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the panel decided that a guideline against the use of GM-CSF mouthrinses in all patients treated with various stomatotoxic CT regimens was not possible, since only one site-specific and highly mucotoxic CT regimen was evaluated in this study. Nicolatou-Galitis et al [57,58] reported results from a case series suggesting a preventative effect of GM-CSF mouthwashes on mucositis in patients receiving RT for H&N cancer, whereas controlled studies by Saarilahti et al and Mantovani et al [59,60] reported only a marginal effect. In contrast, Sprinzl et al [61] found no benefit ( Table 1).…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 94%
“…For example, agents that promote invasion of phagocytic cells into the biofilm, in combination with glycocalyxreducing drugs, may increase the effectiveness of treatment in biofilm-associated skin infections [57]. Along these lines, the beneficial effects of a granulocyte-macrophage colonystimulating factor-based mouthrinse was shown recently in radiation-treated patients with pseudomembranous candidiasis [59].…”
Section: Therapeutic Challenges In Mucosal Biofilm Infectionsmentioning
confidence: 99%